2014
DOI: 10.4314/joafss.v11i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Classification and Land Capability Evalution of Ndoni Meander Belt Soils in Niger Delta.

Abstract: Characterization, classification and land capability evaluation of Ndoni Agroecological zone in the meander belt of the Niger Delta was done. The pedons were identified on the basis of topography, drainage, vegetation, physical, chemical and morphological characteristics. The soil textures were irregular; sandy in the moderately drained levees and recent alluvial deposits but clayey in the poorly drained terrace and backswamps. The soils were generally acid; had moderate to high organic matter, low to moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The amount and distribution of total nitrogen correlated positively with that of organic carbon. This is because the two occur in relatively fixed ratios (Ayolagha and Opene, 2012). Based on the rating by Metson (1961), the soils were very low in nitrogen content.…”
Section: Resultsmentioning
confidence: 99%
“…The amount and distribution of total nitrogen correlated positively with that of organic carbon. This is because the two occur in relatively fixed ratios (Ayolagha and Opene, 2012). Based on the rating by Metson (1961), the soils were very low in nitrogen content.…”
Section: Resultsmentioning
confidence: 99%
“…According to FAO (1990), a silt-clay ratio of less than 0.20 signifies low degree of weathering. However, Ayolagha (2001) posits that old parent materials usually have a SCR below 0.15 while SCR above 0.15 is indicative of young parent materials. Interestingly, results of this study showed that all the soils had silt-clay ratios above 0.2 and 0.15 indicating a high degree of weathering potentials in all the soils.…”
Section: Physical Properties Of the Soilmentioning
confidence: 99%
“…The relative humidity is between 74 to 89%. The area covers the upper deltaic plain that forms a relatively low-lying broad and more gently sloping portion of the Niger Delta basin, comprising small ox-bow lakes, flood plains, alluvial cones, alluvial fans, natural levees of rivers and creeks and back swamps (Mordi, 1986;Ayolagha, 2001;Kamalu et al, 2002). The soils of Bayelsa State Nigeria are derived from geologic materials of Fluvial and alluvial materials (Figure 2) which are recent deposits of alluvium that have been affected only by slight soil forming process such as the incorporation of humus and the development of mottled color owing to poor drainage (Ayolagha, 2001).…”
Section: Study Areamentioning
confidence: 99%
“…The area covers the upper deltaic plain that forms a relatively low-lying broad and more gently sloping portion of the Niger Delta basin, comprising small ox-bow lakes, flood plains, alluvial cones, alluvial fans, natural levees of rivers and creeks and back swamps (Mordi, 1986;Ayolagha, 2001;Kamalu et al, 2002). The soils of Bayelsa State Nigeria are derived from geologic materials of Fluvial and alluvial materials (Figure 2) which are recent deposits of alluvium that have been affected only by slight soil forming process such as the incorporation of humus and the development of mottled color owing to poor drainage (Ayolagha, 2001). The study area is within the equatorial rainforest region though the archetype forests around the lake have been replaced by oil palm (Eliasis guineensis) grooves Raffia palms (Farinifera), and agroforestry species such as Bush mango (Irvingia gabonensis,) Cola sp., Plantain (Musa sp.)…”
Section: Study Areamentioning
confidence: 99%